Effects of Environmental Factors on Anammox Bacterial Community Structure in Sediments of a Freshwater Aquaculture Farm, Yangcheng Lake. Issue 6 (2nd July 2016) - Zhang, Yaping; Ruan, Xiaohong; Wan, Yu; Li, Xiaowan
ABSTRACT: Previous studies have reported wide distribution of anaerobic ammonia oxidation (anammox) bacteria in various ecosystems. However, little is known about the distribution of anammox bacteria under varying environmental conditions in intensive aquaculture systems. In Yangcheng Lake, a famous crab farm situated in the Yangtze River Delta, sediment samples were collected in October (feeding period) and January (nonfeeding period) to analyze the distribution and diversity of anammox bacteria and their relationships with environmental factors. Based on the functional biomarker of Anammox bacteria, hzo gene, anammox bacterial clone libraries were constructed and their abundances were determined by quantitative PCR (qPCR). The Anammox bacteria were detected in the lake with the abundances ranging from 0.70 × 10 5 to 6.05 × 10 5 copies per gram of sediment. Sequences from eight clone libraries yielded seven unique operational taxonomic units (OTUs), distantly related to the Candidatus Jettenia genera with a similarity of about 91%. The Anammox bacterial community structures, diversities and abundances varied spatiotemporally with environmental conditions. In October, the level of the nitrogen compounds, the diversity, evenness and abundance of Anammox bacteria were higher than in January. The predominant OTU of samples changed from HZO-OTU-1 (34.25%) in January to HZO-OTU-2 (28.90%) in October. Moreover, the site (SW) nearing to sewage inlet was lack of HZO-OTU-7 in January. Canonical correspondence analysis (CCA) showed that the pore water NO2 − concentration, ammonium to nitrogen oxides ratio (NH4 + /NOx − ) and total organic carbon to total nitrogen ratio (TOC/TN) contributed most to Anammox bacterial community structures variances. Pearson correlations analysis revealed that the Anammox bacteria abundance had positive co-relationships with TN, NH4 +, NO3 − concentrations, and negative correlation with TOC/TN in porewater.